ARTIFICIALLY INTELLIGENT? Machine Learning in Healthcare and Why It May Not Be As Advanced As You Think. - Choudhury, Avishek; Allen, Caitlyn (Patient Safety (2689-0143))
Machine learning: What exactly is it, and how is it being used in healthcare? Are machines always better than a person? How do we know? Managing editor, Caitlyn Allen, sat down with Dr. Avishek Choudhury, artificial intelligence healthcare researcher, to answer these questions and more.